1999
DOI: 10.2337/diacare.22.9.1422
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and immunologic effects of insulin lispro in gestational diabetes.

Abstract: Insulin lispro may be considered a treatment option for women with gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 0 publications
9
89
0
6
Order By: Relevance
“…Our group has reported that 44% of women receiving human insulin therapy for GDM develop IAs, which may persist up to 24 months after delivery (42). Similar findings have been described after treatment with lispro (43). GADAs and IA-2As.…”
Section: Dras and Diabetic Pregnancysupporting
confidence: 72%
“…Our group has reported that 44% of women receiving human insulin therapy for GDM develop IAs, which may persist up to 24 months after delivery (42). Similar findings have been described after treatment with lispro (43). GADAs and IA-2As.…”
Section: Dras and Diabetic Pregnancysupporting
confidence: 72%
“…The group treated with lispro experienced fewer pre-breakfast hypoglycemic events (<55 mg/dL), but not before lunch or dinner. Mean birth weight, frequency of macrosomia, intrauterine growth restriction (IUGR), and fetal abnormalities did not significantly differ [20].…”
Section: Lispromentioning
confidence: 99%
“…The studies observed postprandial glycemia consistently decreased, particularly 1-hour postprandially [12,20,27,31]. Of the studies that measured fasting glycemia, there were no differences between lispro and regular insulin [12,20,27,31].…”
Section: Lispromentioning
confidence: 99%
See 2 more Smart Citations